Stock price reactions of target firms to mergers and acquisitions in Turkey - Okudan, Sevda (İstanbul Bilgi Üniversitesi, 2017)
[Abstract Not Available]
Türkiye'de şirket birleşme ve satın almaların hedef şirketlerin hisse senedi fiyatlarına etkileri